PENGEMBANGAN MODEL PERMAINAN BOLA BASKET RING DATAR PADA SISWA KELAS VII SMPN SATU ATAP TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to produce a model of learning the game of basketball a basketball game flat ringfor class VII SMP One Roof Lerep Unggaran Western District of Semarang District in teaching physicaleducation . The analysis procedure includes product development product that will be created , developed theinitial product , expert validation and revision , testing and revision of small groups , large groups and test thefinal product . The data was collected using a questionnaire derived from expert evaluation , as well as usingfield observations obtained from the students . The data analysis technique used is descriptive percentages .From the test results obtained by the expert average percentage results of the analysis of the product by 94.2 %with the criteria of " very good " . Therefore, it can be used . Data observations and student questionnaires insmall -scale trials obtained with an average percentage of 86.7 % with the criteria of " good " . Dataobservations and student questionnaires obtained large -scale trials with an average percentage of 87.3 % withthe criteria of " good " . Based on the research data , it was concluded that the development of the game ofbasketball flat ring effectively and in accordance with the characteristics of class VII Junior High School is avery active and playful moves so that it can be used in teaching physical education at the Junior High Schoolseventh grade .